Pressure-induced valence changes of cerium in some cerium-based compounds - Islam, Md Shafiqul; Hossain, Md Tarek; Hannan, Abdul (Journal of Bangladesh Academy of Sciences, 2022)
In the present work, we investigate how pressure affects the valence change of cerium in cerium-based compounds CeX (X= O, S, Te, P, As, Sb, and Bi). The valence of cerium at a certain high pressure is estimated by comparing the experimentally observed unit cell volume and the calculated unit cell volume of stable trivalent cerium ion in the compound. The change in unit cell volume with pressure is estimated by employing the Birch equation of state. It is found that the valence of Ce in the CeX is significantly influenced by both the applied pressure as well as the chemical environment around the Ce ion. J. Bangladesh Acad. Sci. 46(2); 147-154: December 2022